The use of information and communication technology in distance education - Sabrina Bendjama (Social Empowerment Journal, 2020)
This study aims to identify the nature of information and communication technology, and addressing the quality of higher education, and highlights the importance of using the information and communication technology to improve the quality of higher education in Algerian university. The study concluded that the use of information technology in higher education at Algerian university leads to the spread of education and improving the level and reduce Costs, because there are the costs of unforese en and continuous improvement of the role of the teacher and the teaching methods in distance learning and artificial intelligence for education and achieve the brightest possible levels in the practices and processes, and from access to the outputs with bright efficiency.